2008
DOI: 10.1021/mp800024g
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Therapeutics: Targeting Macromolecules and Nanocarriers to Hyaluronan or CD44, a Hyaluronan Receptor

Abstract: The complex system involved in the synthesis, degradation, and binding of the high molecular weight glycosaminoglycan hyaluronic acid (hyaluronan or HA) provides a variety of structures that can be exploited for targeted cancer therapy. In many cancers of epithelial origin there is an up-regulation of CD44, a receptor that binds HA. In other cancers, HA in the tumor matrix is over-expressed. Both CD44 on cancer cells and HA in the matrix have been targets for anti-cancer therapy. Even though CD44 is expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
292
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(297 citation statements)
references
References 85 publications
4
292
0
1
Order By: Relevance
“…Furthermore, beside this targeting advantage, HA-drug conjugates provide advantages in terms of drug solubilization, stabilization, localization and controlled release. Platt and Szoka reviewed a number of HA-drug conjugates for selective CD44 receptor-mediated cell internalization by cells [27]. Once internalized, intracellular enzymes hydrolyze the hydrolytically labile HA-drug bond, thus releasing the drug inside the target cell [28][29][30].…”
Section: Ha Anticancer Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, beside this targeting advantage, HA-drug conjugates provide advantages in terms of drug solubilization, stabilization, localization and controlled release. Platt and Szoka reviewed a number of HA-drug conjugates for selective CD44 receptor-mediated cell internalization by cells [27]. Once internalized, intracellular enzymes hydrolyze the hydrolytically labile HA-drug bond, thus releasing the drug inside the target cell [28][29][30].…”
Section: Ha Anticancer Drugmentioning
confidence: 99%
“…Beyond paclitaxel, other anticancer agents were successfully linked to HA, aiming to overcome toxicity and to confer new physico-chemical characteristics [27,28,[46][47][48]. Adipic acid dihydrazide and succinic anhydride were used as spacers to connect 5-fluro uracil (5-FU) to HA, reaching a loading of 8 mol %.…”
Section: Ha Anticancer Drugmentioning
confidence: 99%
“…For instance, hyaluronic acid has been used to transport chemotherapeutic drugs. 8 It has been shown to be useful when administered intraperitoneally for improving the effects of paclitaxel in gastric cancer. 9 Furthermore, an experimental study of hyaluronic acid-conjugated butyric acid has showed rapid cellular uptake in a human breast carcinoma cell line.…”
Section: Hyaluronic Acid and Nanomedicinementioning
confidence: 99%
“…Ahrens et al reported that the hyaluronan receptor, CD44, is a mediator for proliferation and metastasis of malignant melanoma (40). Furthermore, it has been demonstrated that proliferation and metastasis of tumors can be suppressed by administering anti-CD44 antibodies to the body, and the clinical application of this method has been rapidly promoted (41).…”
Section: Mu(-)mentioning
confidence: 99%